Political Economy of Soviet Military Power - Cooper, Leo. author. aut Link
XI, 263 p.
Keywords: A study of the political economy of Soviet military power, examining Soviet Russian ideology and tradition, theory and practice of the military doctrine, the domestic aspect and new economic realism, technology and efficiency, and Perestroika and Glasnost from 1985-1987.